A Yoga programme approaches for pregnancy-related low back and pelvic pain - Nurwinda Saputri; Dzul Istiqomah Hasyim; Rita Sari (Program Studi Ilmu Keperawata Fakultas Kedokteran Universitas Malahayati Bandar Lampung, 2021)
Background: One of the most common discomforts during pregnancy is relating to low back and pelvic pain. Predisposing factors include uterine growth that causes posture changes, weight gain, the influence of relaxin hormone on ligaments, previous history of back pain, parity and activity. The exercise that helps pregnant women get a power to facilitate the delivery process by a Yoga programme approaches.Purpose: To determine the effect of a Yoga programme approaches for pregnancy-related low back and pelvic painMethod: A quantitative research method. The study population was third trimester pregnancy, taken by purposive sampling technique, and got a sample of 22 participants and Questionnaire used as the research instrument test. The analysis technique used in this research is descriptive quantitative.Results: Finding that the average score of low back and pelvic pain before a Yoga programme (pre test) was 3.73 (moderate pain) with a standard deviation of 1.38. The average score after intervention at the post-test stage was 1.14 (mild pain) with a standard deviation of 0.94. (p value = 0.000 <0.05).Conclusion: There is an effect of a Yoga programme approaches for pregnancy-related low back and pelvic pain in third trimester pregnancy